The Spillover Effect of Urban Village Removal on Nearby Home Values in Beijing. (22nd July 2015) - Zhang, Yingjie; Zheng, Siqi; Song, Yan; Zhong, Yongguang
Abstract: An urban village is a typical type of informal housing settlement in which rural migrants stay in Chinese cities. As urban villages are being woven into modern urban landscapes, we estimate the size of their negative externality and also the positive spillover effect of their removal on nearby formal housing communities. We employ two micro data sets: one includes all the existing urban villages in 2006 and a unique micro survey of 50 villages conducted in 2008, and the other contains 24, 000 micro resale records in the formal housing sector from 2006 to 2011. Our findings show that an average urban village causes a 2.5 percent housing price discount in nearby communities, and the removal of this urban village triggers a 3.3–4.3 percent housing price appreciation. However, more careful consideration is needed for the other side of the coin—the welfare change of those rural migrants who are displaced during this process.